Digitisasi Arsip di Warung Arsip Yogyakarta: Analisis Peluang dan Tantangan Menggunakan SWOT - Lia Nur Faizah; Thoriq Tri Prabowo (Khazanah: Jurnal Pengembangan Kearsipan, 2022)
This study aims to describe digitization activities at Warung Arsip Yogyakarta. In addition, this study will also describe the opportunities and challenges of the digitization activity using a SWOT analysis. This study uses descriptive qualitative methods. Collecting data process conducted by observation, interviews, and documentation. The data analysis technique was done several acivities sort of: data reduction, data display, and conclusion drawing. The digitization process at Warung Arsip Yogyakarta uses two methods, namely pemindaian for publications such as magazines; and capturing pictures for publications such as newspapers. The digitization process is experiencing problems due to lack of human resources (HR) and limited digital archive storage. Warung Arsip Yogyakarta are taking advantage of relationship opportunities to reach more information, maximizing creativity in digitizing newspapers, upgrading the digital archive storage system. In an effort to face the challenges, Warung Arsip Yogyakarta needs to carry out promotions to increase public interest in archives, create a special room for archives that have not been digitized, carry out periodic cleaning, make SOPs for archive maintenance, and recruit employees.